A Force Balanced Fragmentation Method for ab Initio Molecular Dynamic Simulation of Protein - Xu, Mingyuan; Zhu, Tong; Zhang, John Z. H. (Frontiers in Chemistry, 2018)
A force balanced generalized molecular fractionation with conjugate caps (FB-GMFCC) method is proposed for ab initio molecular dynamics simulation of proteins. In this approach, the energy of the protein is computed by a linear combination of the QM energies of individual residues and molecular fragments that account for the two-body interaction of hydrogen bond between backbone peptides. The atomic forces on the caped H atoms were corrected to conserve the total force of the protein. Using this approach, ab initio molecular dynamics simulation of an Ace-(ALA)9-NME linear peptide showed the conservation of the total energy of the system throughout the simulation. Further a more robust 110ps ab initio molecular dynamics simulation was performed for a protein with 56 residues and 862 atoms in explicit water. Compared with the classical force field, the ab initio molecular dynamics simulations gave better description of the geometry of peptide bonds. Although further development is still needed, the current approach is highly efficient, trivially parallel, and can be applied to ab initio molecular dynamics simulation study of large proteins.